1918
DOI: 10.1098/rspa.1918.0055
|View full text |Cite
|
Sign up to set email alerts
|

Sounds produced by drops falling on water

Abstract: To sum up the chief points of the second paper :-(1) The rate of evolution or absorption of heat by quenched steel is, after a short initial period, approximately in inverse ratio to the time elapsed after quenching.(2) The actual rate of evolution has been determined for various specimens.(3) The rate of contraction of quenched steel was found to follow the same law as the rate Of evolution or absorption of heat.(4) This suggests that the contraction is intimately connected with the heat evolution, both being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1927
1927
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In the experiments reported here, a similar smooth funnel shape is seen for the lighter spheres and the lower drop heights; similar shapes are seen in water (see e.g. [3]) and polymer fluids [23]. The pinch-off process for the smooth, viscous-like cavity in a wormlike micellar fluid is shown for a d = 2.54 cm delrin sphere in Fig.…”
Section: Surface Deformation and Cavity Dynamicssupporting
confidence: 67%
See 2 more Smart Citations
“…In the experiments reported here, a similar smooth funnel shape is seen for the lighter spheres and the lower drop heights; similar shapes are seen in water (see e.g. [3]) and polymer fluids [23]. The pinch-off process for the smooth, viscous-like cavity in a wormlike micellar fluid is shown for a d = 2.54 cm delrin sphere in Fig.…”
Section: Surface Deformation and Cavity Dynamicssupporting
confidence: 67%
“…Recently, similar forward-pointed bubbles were seen numerically in a two-dimensional geometry of an axially oriented nematic liquid crystal. 3 We expect a similar explanation here: that the flow-induced structures in the wake of the sphere [11] lead to a local micellar orientation which produces this pointed shape. Note that the bubble does also have a trailing edge cusp-like tail, as is seen in polymer fluids [56], and in fact jumps as it rises, as smaller bubbles do in wormlike micellar fluids [15,16].…”
Section: Appendix Amentioning
confidence: 62%
See 1 more Smart Citation
“…Subsequent studies by Mallock (1918) and Bell (1924) provided some qualitative explanation for the observed cavity shapes and sphere trajectories. The advent of high-speed cine-photography allowed for quantitative measurements, the first series of which explored the influence of the atmospheric pressure on the water entry of missiles (Gilbarg & Anderson 1948;Richardson 1948).…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of projectiles into liquid surfaces during gravity were intensively studied in the early 20th century (Mallock 1918;Birkhoff 1960). Experiments showed that, at low impact velocities, the fluid surface seals deep while at entry velocities above 40 km/h, the fluid seals at the surface due to air pressure.…”
Section: Resultsmentioning
confidence: 99%